Hepatocellular adenoma classification: a comparative evaluation of immunohistochemistry and targeted mutational analysis. Issue 1 (December 2016) - Margolskee, Elizabeth; Bao, Fei; de Gonzalez, Anne; Moreira, Roger; Lagana, Stephen; Sireci, Anthony; Sepulveda, Antonia; Remotti, Helen; Lefkowitch, Jay; Salomao, Marcela
Abstract Background Four subtypes of hepatocellular adenomas (HCA) are recognized: hepatocyte-nuclear-factor-1α mutated (H-HCA), β-catenin-mutated type with upregulation of glutamine synthetase (b-HCA), inflammatory type (IHCA) with serum-amyloid-A overexpression, and unclassified type. Subtyping may be useful since b-HCA appear to have higher risk of malignant transformation. We sought to apply subtype analysis and assess histological atypia, correlating these with next-generation sequencing analysis. Methods Twenty-six HCA were stained with serum amyloid A (SAA), liver fatty acid-binding protein (LFABP), glutamine synthetase (GS), and β-catenin IHC, followed by analysis with a targeted multiplex sequencing panel. Results By IHC, 4 HCA (15.4 %) were classified as b-HCA, 11 (42.3 %) as IHCA, 9 (34.6 %) as H-HCA, and two (7.7 %) unclassifiable. Eight HCA (30.8 %) showed atypia (3 b-HCA, 4 IHCA and 1 H-HCA). Targeted sequencing confirmedHNF1A mutations in all H-HCA, confirming reliability of LFABP IHC in identifying these lesions.CTNNB1 mutations were detected in 1 of 4 (25 %) of GS/β-catenin-positive cases, suggesting that positive GS stain does not always correlate withCTNNB1 mutations. Conclusions Immunohistochemistry does not consistently identify b-HCA. Mutational analysis improves the diagnostic accuracy of β-catenin-mutated HCA and is an important tool to assess risk of malignancy in HCA.